Plurality of Lesbian Movements under Hatred-Epidemic: Initiation of SOGIE Advocacy in Nusantara - Gayatri, BJD. (Jurnal Perempuan, 2015)
This paper is an overview toward SOGIE (Sexual Orientation, Gender Identity and Expression). This charted the history of lesbianism in Indonesia. Approach being used is feminist personal history. There are two approaches in advocy of human-right based SOGIE. First, the advocacy toward KUHP (product of law) that is based on positive and gender-normative that will endangered the existence of LGBT in Indonesia. Second, SOGIE-activists shall understand fully the plurality of gender and sexuality that is homegrown in Indonesia. This is the best way to advocate the rights as an integral part of Nusantara culture.